Peran Guru dalam Pengembangan Kurikulum Pembelajaran - Abdullah, Ahmad Afif; Ahid, Nur; Fawzi, Tanya; Muhtadin, Muhammad Akhsanul (Lembaga Yasin AlSys, 2023)
The curriculum as an instructional design occupies a very strategic place in all aspects of educational activities. Given the importance of curriculum development in education, the preparation must refer to a solid foundation. The basis for program formation is not only needed for program designers (macro) or programmers, who are often called ideal programs, but also must be understood and used as a basis for implementing (micro) study programs, especially pedagogical advisers, teachers and other stakeholders related to management tasks. education, as a guiding tool for the implementation of educational programs at every type and level of education. With this important position, program development cannot be carried out haphazardly, but must be based on different considerations, or on the basis of taking it as the basis for implementing the educational process, in order to facilitate its implementation more efficiently and effectively. effective programme. effective educational and learning goals. As a professional teacher, a teacher must not only have professional competence but also professional knowledge and skills. Teachers must master or understand curriculum and textbooks as tools to promote teaching and learning. Many people think that being an educator is easy, but being a teacher requires understanding and developing curriculum.